2018
DOI: 10.1097/meg.0000000000001018
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18-fluorodeoxyglucose uptake of bone marrow on PET/CT can predict prognosis in patients with colorectal cancer after curative surgical resection

Abstract: Increased BM SUV was observed in patients with advanced stage and increased serum inflammatory markers. BM SUV was an independent predictor for RFS in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 31 publications
7
27
0
Order By: Relevance
“…In several types of cancer, increased FDG avidity of the bone marrow seemed to be associated with prognostic factors such as lower overall survival rate and higher cancer recurrence rate [9][10][11][12][13][14]. In our cohort of patients with bacteremia, BLR or SLR was not associated with a total duration of hospital stay, ICU admission, or mortality.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In several types of cancer, increased FDG avidity of the bone marrow seemed to be associated with prognostic factors such as lower overall survival rate and higher cancer recurrence rate [9][10][11][12][13][14]. In our cohort of patients with bacteremia, BLR or SLR was not associated with a total duration of hospital stay, ICU admission, or mortality.…”
Section: Discussionmentioning
confidence: 52%
“…The bone marrow and spleen are generally regarded as "hypermetabolic" when their FDG avidity exceeds that of the liver (bone marrow/liver ratio or spleen/liver ratio > 1.0) [8]. Hypermetabolism of the bone marrow or spleen has been associated with laboratory values such as C-reactive protein or hemoglobin and even prognosis in patients with several types of cancer [9][10][11][12][13][14] and autoimmune disease [15,16]. However, the clinical and pathophysiological meaning of hypermetabolism of the bone marrow and spleen in patients with bacteremia is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The present study found that BLR measured on pre- F]FDG uptake of BM in a significant portion of patients with malignant diseases, even in those without concurrent infectious or hematologic diseases [23,24]. Previous studies reported that BM SUV and BLR have significant positive correlations with white blood cell counts, serum C-reactive protein level, NLR, PLR, and transforming growth factor (TGF)-beta [14,[16][17][18][19][24][25][26]. A number of previous studies have demonstrated that PET parameters of BM were significant predictors for survival in various kinds of cancers including small cell lung cancer, non-small cell lung cancer, gastric cancer, cervical cancer, colorectal cancer, lymphoma, malignant pleural mesothelioma, melanoma, and head and neck cancer [14, 17-19, 23-25, 27-32].…”
Section: Discussionmentioning
confidence: 72%
“…Because [ 18 F]FDG uptake of BM mainly reflects glucose metabolism of immune cells, increased [ 18 F]FDG uptake of BM in patients with malignant diseases is considered to be due to BM activation caused by host inflammatory response [15,16]. In various malignant diseases, [ 18 F]FDG uptake of BM has shown significant correlations with serum inflammatory markers and clinical outcomes [14,[17][18][19][20]. However, in patients with breast cancer, only a single study have evaluated the clinical implication of [ 18 F]FDG uptake of the reticuloendothelial system including BM and the spleen [21], and the prognostic potential of [ 18 F]FDG uptake of BM for predicting distant recurrence has not been reported yet.…”
mentioning
confidence: 99%
“…The remaining 10 articles had their bibliographies reviewed in a systematic manner. This identified a further 2 articles to be included in the final analysis, leading to final figure of 12 articles considered in the present systematic review (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Study Selection Processmentioning
confidence: 99%